Pigeon Stories: Review of Colin Jerolmack, The Global Pigeon - Holmberg, Tora (Humanimalia, 2013)
Colin Jerolmack. The Global Pigeon. Fieldwork Encounters and Discoveries. Chicago: The University of Chicago Press, 2013. 288 pp. $80.00 hb; $27.50 pb; $7.00-$27.00 e-bk.